PENGARUH KOMITMEN DAN KOMPETENSI TERHADAP KINERJA GURU DIMODERASI SUPERVISI - Rodhi, Rodhi (Students Journal of Economic and Management, 2012)
This study aims to analize the influence of commitment and competence of teacher on teacher performanceÂ moderated by headmaster supervision in elementary school teachers with the status of Civil Servants (PNS) at UPT Disdikpora Gringsing Regency, Batang District. Population in this research are elementary school teachers civil Servants amounted to 178 people. The number of samples in this study were 124 people. Measurement of responses to questionnaires using a likert scale of 7 (seven) alternative answer. Testing instrument using validity and reliability, are testing a model using the coefficient of determination and the F test (Goodness of Fit). Testing hypothesesÂ in this study using regression quasy interactions with significance level (Î±) 5%. The results showed 51,6% of the change in teacher performance variable can be explained by the influence of commitment, competence, supervision, commitment and supervision interaction, and competence and supervision interaction, was 48,4% explained outside the model. The results of hypotheses testing obtained the results that school commitment positively and significance effect of the teacher performance, competence positively and significance effect of the teacher performance, supervision unsignifiance effect of the teacher performance, supervision weaknessthen the influence school commitment on teacher performance, and supervision weaknessthen the influence competence on teacher performance. Keywords: commitment, competence, supervision, teacher performance